Hartmann's procedure versus intersphincteric abdominoperineal excision (HiP Study): a multicentre prospective cohort study. (2nd October 2020) - Fowler, H.; Clifford, R.; Sutton, P.; Watson, A.; Fearnhead, N.; Bach, S.; Moran, B.; Rose, A.; Jackson, R.; Vimalachandran, D.; ,
Abstract: Aim: In patients with low rectal cancer it is occasionally necessary to avoid a low coloanal anastomosis due to patient frailty or poor function. In such situations there are two alternative approaches: Hartmann's procedure (HP) or intersphincteric abdominoperineal excision (IAPE). There are few data to guide surgeons as to which of these two procedures is the safest. The aim of this study was to determine the surgical complication rates associated with each procedure. Method: This was a multicentre, nonrandomized prospective cohort study of patients undergoing either HP or IAPE. The primary objective was to determine surgical complication rates. Secondary objectives included length of stay, time to adjuvant therapy and quality of life at 90 days. Results: One hundred and seventy nine patients were recruited between April 2016 and June 2019; approximately two thirds of patients underwent HP and one third IAPE. The overall complication rate was high in both groups (54% for the HP group and 52% for the IAPE group). Surgery‐specific complication rates were also high, but not significantly different: 43% for HP and 48% for IAPE. The pelvic abscess rate in HP was 11% and was significantly higher in patients with a palpable staple line (15% vs 2%). There was a higher incidence of serious medical complications following IAPE (16% vs 5%), along with a reduction in 90‐day quality of life scores. Conclusion: This is the largest prospective study to compare HP and IAPE in patients undergoing rectal cancer surgery where primary anastomosis is not deemed appropriate. With similar complication rates, these data support the ongoing use of either HP or IAPE in this patient group.